Informative assessment: A supportive tool for systemic validity in language education - du Plessis, C.L.; Els, C. (South African Journal of Higher Education, 2020)
Abstract Accountability in language testing is normally supported through a validation process. In language teaching, however, the matter of accountability is sometimes overlooked, especially when the focus falls on curriculum completion. In view of the reciprocity that exists between language teaching and testing, core principles used for test validation are also useful for ensuring accountability in course design. This paper evaluates a language course offered to Education students at a tertiary institution by drawing on the notions of construct and content validity. Empirical data gleaned from a literacy survey and assessment artefacts are interpreted against course objectives and content. A need is identified for substantial revisions to the course in order to ensure closer alignment with students’ language learning needs. The study shows how accountability in language education coheres with the principle of systemic validity and the relevance of analysing and correlating different kinds of data.